A Western-Fed Diet Increases Plasma HDL and LDL-Cholesterol Levels in ApoD–/– Mice - Ali, Kamilah (PLoS One, 2014)
OBJECTIVE: Plasma apolipoprotein (apo)D, a ubiquitously expressed protein that binds small hydrophobic ligands, is found mainly on HDL particles. According to studies of human genetics and lipid disorders, plasma apoD levels positively correlate with HDL-cholesterol and apoAI levels. Thus, we tested the hypothesis that apoD was a regulator of HDL metabolism. METHODS & RESULTS: We compared the plasma lipid and lipoprotein profiles of wild-type (WT) C57BL/6 mice with apoD−/− mice on a C57BL/6 background after receiving a high fat-high cholesterol diet for 12 weeks. ApoD−/− mice had higher HDL-cholesterol levels (61±13-apoD−/− vs. 52±10-WT-males; 37±11-apoD−/− vs. 22±2 WT-female) than WT mice with sex-specific changes in total plasma levels of cholesterol and other lipids. Compared to WT, the HDL of apoD−/− mice showed an increase in large, lipid-rich HDL particles and according to size various quantities and sizes of LDL particles. Plasma levels of lecithin:cholesterol acyltransferase in the control and apoD−/− mice were not different, however, plasma phospholipid transfer protein activity was modestly elevated (+10%) only in male apoD−/− mice. An in vivo HDL metabolism experiment with isolated Western-fed apoD−/− HDL particles showed that female apoD−/− mice had a 36% decrease in the fractional catabolic rate of HDL cholesteryl ester. Hepatic SR-BI and LDLR protein levels were significantly decreased; accordingly, LDL-cholesterol and apoB levels were increased in female mice. CONCLUSION: In the context of a high fat-high cholesterol diet, apoD deficiency in female mice is associated with increases in both plasma HDL and LDL-cholesterol levels, reflecting changes in expression of SR-BI and LDL receptors, which may impact diet-induced atherosclerosis.